Peningkatan Kompetensi Guru Dalam Pembelajaran Pada Sekolah Menengah Bermutu Di Pamekasan - Buna'i Buna'i (TADRIS: Jurnal Pendidikan Islam, 2018)
Abstract:The purpose of this study is to describe and explain the program, pattern and evaluation of improving teacher competency in learning in MAN Pamekasan, SMAN 1 Pamekasan, and SMK 3 Pamekasan. This study uses a qualitative approach with multicasus types and uses interview methods, participant observation, and documentation in the data collection. The results of this study are: increasing teacher competency has been programmed every year by involving many parties. Improving teacher competency in accordance with the plan in the form of coaching, further education, education and training, and professional activities. The teacher responds positively to improving teacher competence. This can be seen from the attitude of teachers who are happy, enthusiastic and active in the activities they teach. While the constraints faced in improving teacher competencies are: limited budget owned by the school, limited facilities / infrastructure owned by the school and teachers, lack of time to conduct training, and diversity of teacher characteristics. The solution is to overcome obstacles, namely: proposing additional budgets to the government, cooperating with third parties, discussing with school committees, motivating teachers to maximize existing facilities/infrastructure, building harmonious and democratic relationships with teachers, and utilizing time effectively. In each semester an evaluation of teacher competencies has been carried out by the team. The results of evaluating teacher competency improvement show good results. Follow-up program in the form of awards and guidance to teachers.